Mobile emergency rule in Turkey: legal repression of protests during authoritarian transformation. Issue 6 (17th August 2020) - Arslanalp, Mert; Deniz Erkmen, T.
ABSTRACT: One of the challenges of autocratizing governments in regimes with nominally democratic institutions is how to repress fundamental democratic rights while claiming to uphold the rule of law. Post-9/11 socio-legal debates point to the emergency rule as a legal framework within democratic constitutions that can be potentially used to hollow out citizens' rights. But the study of emergency rule is often limited to its enactment under extraordinary situations. This article takes the crucial case of Turkey's authoritarian transformation and develops the concept of mobile emergency rule to argue that emergency-like suspensions of rights also occur in highly localized and temporary forms in the absence of an officially declared state of emergency. Based on an original dataset, it examines all legal bans on protests issued by authorities between 2007 and 2018 in the name of maintaining order and security. The results illustrate how the use of this tool dovetailed with key turning points of authoritarian transformation in Turkey and reflected the changing needs of the regime as it tried to build and sustain a new hegemonic project. In effect, mobile emergency rule created a highly ambiguous terrain for protest rights even before the declaration of state of emergency in July 2016.